PENGARUH MASYARAKAT TERHADAP TINGKAH LAKU WANITA PADA PRIA DALAM NOVEL THE GREAT GATSBY KARYA F. SCOTT FITZGERALD - LAMUSUDIDI, NUR AISYA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT Â  The title of this research is â€œThe Influence of Society on Womenâ€™s Attitude toward Men in the Novel The Great Gatsby by F. Scott Fitzgeraldâ€. The objectives of this research are to analyze the attitude of women toward men in The Great Gatsby and to analyze how the society influences this particular attitude. The data are collected by focusing on the attitude of women toward men and how the society gives influence on their attitude. By using descriptive method, the writer uses instrinsic approach to analyze the attitude of women toward men, and uses extrinsic method to analyze the influence of society on the attitude of women toward men in the novel. The result of this research shows that the women in The Great Gatsby are commonly full of confidence, they are free to express their opinion, modern, agressive, extravagant, matrealist and they love big parties so much. All of this attitude are appropriate with the society of New York at that time, when it was 1922. The conclusion of this research is that the society when The Great Gatsby was written really has big influence onÂ  the attitude creation of women in the novel. Â  Keywords: Attitude, Society Influence and The Great Gatsby.